2022
DOI: 10.3390/molecules27217497
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Stage Culture Strategy for Scenedesmus sp. FSP3 for CO2 Fixation and the Simultaneous Production of Lutein under Light and Salt Stress

Abstract: In this study, Scenedesmus sp. FSP3 was cultured using a two-stage culture strategy for CO2 fixation and lutein production. During the first stage, propylene carbonate was added to the medium, with 5% CO2 introduced to promote the rapid growth and CO2 fixation of the microalgae. During the second stage of cultivation, a NaCl concentration of 156 mmol L−1 and a light intensity of 160 μmol m−2 s−1 were used to stimulate the accumulation of lutein in the microalgal cells. By using this culture method, high lutein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…Accordingly, this results in an increase in the size of the PSI light-harvesting antenna, and lutein, a light-harvesting pigment bound to a natural protein at the L1 site, will be elevated as the antenna protein level increases [45]. Two-stage culture approaches have been widely applied to enhance biomass and lutein production in microalgae [23,25,37]. Usually, in the first stage, microalgae accumulate biomass rapidly, and when the maximum biomass concentration is reached, the cells are transitioned to the second stage to accumulate the desired compound.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Accordingly, this results in an increase in the size of the PSI light-harvesting antenna, and lutein, a light-harvesting pigment bound to a natural protein at the L1 site, will be elevated as the antenna protein level increases [45]. Two-stage culture approaches have been widely applied to enhance biomass and lutein production in microalgae [23,25,37]. Usually, in the first stage, microalgae accumulate biomass rapidly, and when the maximum biomass concentration is reached, the cells are transitioned to the second stage to accumulate the desired compound.…”
Section: Discussionmentioning
confidence: 99%
“…F51 resulted in a lutein content of 5.05 mg g −1 and lutein productivity of 3.56 mg −1 L −1 d −1 . Li et al [23] reported a two-stage culture of Scenedesmus sp. FSP3, achieving the highest lutein content and productivity of 6.45 mg g −1 and 3.36 mg L −1 , respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These factors include algae strain growth rates and CO2 uptake efficiency, design of the bioreactors, nutrient availability in the wastewater, soil fertility, biomass productivity, and site-specific conditions. Therefore, as a rough initial estimation, literature data is used with the following considerations (Bai et al, 2017;Ghorbani et al, 2014;Li et al, 2022;LTD. ), n.d.; Pavlik et al, 2017;Politaeva et al, 2023):…”
Section: Co2 Biofixationmentioning
confidence: 99%